POLICY SHORTCOMINGS AFFECTING TRADITIONAL MALE CIRCUMCISION (TMC) IN THE EASTERN CAPE PROVINCE - Nomngcoyiya, Thanduxolo; Kang’ethe, Simon (Social Work/Maatskaplike Werk, 2019)
The study took the form of a qualitative empirical case study in order to carry out a critical analysis of the shortcomings of existing policy pertaining to traditional male circumcision (TMC) in the Eastern Cape province of South Africa. Interview guides were developed to conduct in-depth interviews and focus group discussions with 28 participants. Among the principal conclusions from the findings were evidence of a lack of clarity on performing TMC operations, diverging perceptions of policy pertaining to TMC, unclear selection criteria for practitioners, and a lack of enforcement of policies which have been formulated. Recommendations are offered on the basis of the conclusions.